THE USE OF QUESTIONING THE AUTHOR (QtA) STRATEGY IN IMPROVING STUDENTS’ ABILITY IN READING DESCRIPTIVE TEXT AT THE SEVENTH GRADE STUDENTS OF SMP ISLAM PLUS JANNATUL FIRDAUS PEKANBARU - Wahyu Presetyo; M. Fadhly Farhy Abbas (ELT-Lectura, 2017)
Students at SMP Islam Plus Jannatul Firdaus Pekanbaru had problems in understanding the text when reading process, those were because: the students ought to construct of generic structure of descriptive text namely identification and description. The students ought to comprehend the contents of identification. The students ought to comprehend the contents of description. Then, the researcher tested based-score of reading descriptive text, the researcher found that the students’ mean score was just 68. This research aimed to improve the students’ ability in reading descriptive text by using Questioning the Author (QtA) Strategy. Thus, this research conducted Classroom Action Research (CAR) consisting of one cycles. There were 15 students at Grade VII of SMP Islam Plus Jannatul Firdaus Pekanbaru as the participants of the research. To gain the data, the researcher used four instruments namely: test, observation, field note, and interview. The result of the reading test in cycle 1 (78.33) was better than the based-score. The factors influeced the changing of students’ ability in reading descriptive text were the vocabulary mastery, the condition of the class, and absolutely the strategy used by the teacher in teaching reading. In conclusion, Questioning the Author (QtA) strategy can improve the students’ ability in reading descriptive text.